Snow and ice as a resource for innovative tourist experiences in northern Sweden : the case of Ice Theater and Ice Music Hall - Gelter, Hans (Luleå tekniska universitet, Medier, ljudteknik och teater, 2008)
This report of two innovative snow construction projects that border-cross the traditional cultural context of theatre and music with snow and ice shows the great experiential and touristic potential of such projects. At the same time several problems are associated with such projects. The most obvious that resulted in financial problems both with the Ice Dome Theatre at Jukkasjärvi and the Ice Music Concert Hall in Piteå are the high construction and production costs compared with the relative limited income during a short period available for performances. This problem is accentuated by climate change problems where the winter season even in northern Sweden appear to become more unstable affecting the time available for the return of cost. This has Linhart solved by constructing the Ice Dome Concert Hall at 3200 meters elevation, which however result in other problems such as access and material transport costs as well as high altitude fatigue among workers, musicians and audience. The projects have however taught us that high quality experiences can be produced based on traditional cultural art in combination with snow and ice. Further research on methods to reduce both construction and production costs and as well as the economical calculations and project management for such projects should be initiated. Godkänd; 2008; 20081203 (hage) Snö och is som innovativ resurs för besöksnäringen